Transformasi Pakaian Tradisional di Universitas Jember: Pengaruh Budaya Luar Terhadap Pakaian Tradisional - Graha, Rama Dwi Rendra; Saputra, Fiyoga Bayu; Putra, Dwi Wahyu Maulana (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research explores changes in fashion styles among Jember University students in the digital era, which are influenced by social media, digital platforms and international cultural migration. Traditional clothing styles have undergone significant changes due to the influence of foreign cultures in design and materials. Students, as active users of social media and the internet, are the main targets of this change, often exposed to the latest fashion trends and campus events that demand a fashionable appearance. Interviews with two FISIP students at the University of Jember revealed that social media greatly influences the way they dress, reflecting Jean Baudrillard's theory about consumer society. According to Baudrillard, consumption not only fulfills basic needs but also functions as a symbol of identity and social status. Jember University students follow fashion trends to express themselves and demonstrate social affiliation, despite facing challenges such as financial management and disrupted academic priorities. This research uses a case study-based qualitative approach, with semi-structured interviews and field observations to obtain in-depth data. Thematic analysis was carried out to identify main themes such as economic conditions, the influence of fashion trends, and the role of social media. This research shows that changes in student fashion styles are not only a fashion phenomenon, but also reflect broader social and cultural dynamics in the digital era. Baudrillard's theory provides a foundation for understanding how symbolic consumption and the influence of social media influence college students' clothing style choices, as well as their impact on their cultural and socio-economic identities.